Antithrombin III Concentrates-Are they Clinically Useful? - Lechner, K; Kyrle, P A (Thrombosis and Haemostasis, 1995)
Treatment with AT III concentrates is a good example for the discrepancy between the optimistic expectations based on theoretical considerations or animal experiments and the result of clinical studies. 15 years after the introduction into clinical practice, a benefit for patients treated with AT III concentrates has not been proven. In hereditary antithrombin III deficiency, randomized clinical trials are completely lacking and only few and small sized randomized studies were performed in patients with acquired AT III deficiency. In none of these trials, a significant clinical benefit with regard to reduction of morbidity or mortality was detectable. Based on the published data, one can state that AT III concentrates may be beneficial in some special clinical situations in patients with hereditary antithrombin III deficiency (such as delivery, acute serious thromboembolic complications and postoperative thromboprophylaxis). In acquired AT III deficiency, there is no proven indication for the use of AT III concentrates.